International job search - Zikic, J.; Kent, D.; Richardson, Julia (2014)
© Oxford University Press 2018. All rights reserved. As globalization and integration of national economies continues unabated, an increasing number of people are looking for work outside oftheir home countries. Moreover, rather than waiting to be sent overseas by an employer, as might be the case for corporate expatriate assignees, a growing number of people are independently engaging in international job search. In this chapter, we review the literature on these international job seekers, focusing specifically on immigrants and self-initiated expatriates. First, we consider the diverse motives and contextual factors that drive this international job search; second, we look at the personal and cultural factors serving as antecedents for specific job-search behaviors. We then consider how job-search behaviors-in combination with personal factors and host country contexts-influence international job-search outcomes. Throughout this discussion we identify similarities and differences between immigrants and self-initiated expatriates while acknowledging that the boundaries between different groups of international job seekers are blurred. We conclude the chapter with a discussion of areas for future research.